2020
DOI: 10.1002/jmv.26003
|View full text |Cite
|
Sign up to set email alerts
|

Hypoalbuminemia predicts the outcome of COVID‐19 independent of age and co‐morbidity

Abstract: The coronavirus disease 2019 has evolved into a pandemic rapidly. Most of the literature show that the elevated liver enzymes in COVID-19 are of little clinical significance. Lower albumin level is seen in severe COVID-19 and is not parallel to the changes in alanine aminotransferase and aspartate aminotransferase levels. We aimed to explore the impact of hypoalbuminemia in COVID-19. This retrospective cohort study included adult patients with confirmed COVID-19. The relationship between hypoalbuminemia and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
280
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 301 publications
(316 citation statements)
references
References 29 publications
32
280
2
2
Order By: Relevance
“…25 Furthermore, the decreased level of ALB suggests the hypercoagulable state and blood clots condition, which increases the risk of adverse clinical outcomes in COVID-19 patients. 26 In addition, we found that some patients with DIC had hypoxia on admission. Hypoxia deregulates platelet function through enhancement of platelet adhesion, aggregation, and release, which ultimately activates intravascular coagulation and causes the formation of thrombus.…”
Section: Discussionmentioning
confidence: 85%
“…25 Furthermore, the decreased level of ALB suggests the hypercoagulable state and blood clots condition, which increases the risk of adverse clinical outcomes in COVID-19 patients. 26 In addition, we found that some patients with DIC had hypoxia on admission. Hypoxia deregulates platelet function through enhancement of platelet adhesion, aggregation, and release, which ultimately activates intravascular coagulation and causes the formation of thrombus.…”
Section: Discussionmentioning
confidence: 85%
“…Although the mechanisms for hypoalbuminemia in COVID-19 have not been studied thoroughly 24 , albumin is a major serum protein produced by hepatic cells 24,25 and has a critical role in human health.…”
Section: Resultsmentioning
confidence: 99%
“…In most prognostic prediction models that have been published, older age, comorbidities, and increases in lactate dehydrogenase, lymphocyte, and C-reactive protein levels were the risk factors for poor prognosis [25]. Other indicators such as heart rate; breath rate; oxygen saturation; levels of procalcitonin, direct bilirubin, albumin, and D-dimer levels; activated partial thromboplastin time; glomerular ltration rate; and chest radiography abnormality have controversial conclusions [35,36]. Our study also demonstrated that patients with COVID-19 infection who were older (especially >65 years) had a worse prognosis than younger patients.…”
Section: Discussionmentioning
confidence: 99%